Sulbactam+Cefoperazone in Treatment of Complicated Urinary Tract Infections - Yalçın, Orhan; Tahmaz, Lütfü; Bilgiç, İdris; Yılmaz, Mustafa (Kocaeli Üniversitesi, 1996)
The clinical efficacy and safety of sulbactam+cefoperazone combination was evaluated 30 patients suffering from serious urinary tract infection, complicated with urinary tract obstruction. All of the patients who were operating lists, with proven urinary tract infection were given a total daily dose of 2 gr sulbactam combined with 2 gr cefoperazone. Drug administration continued for jive days intravenously twice daily. A 90 percent bacteriological eradication of the isolates was achieved and no significant side effects. Results of the bacteriological studies together with the clinical course of patients confirmed excellent therapeutic efficacy and safety of this drug.

Sulbaktam + Sefoperazon kombinasyonunun etkinliği ve klinik güvenilirliği, üriner sistem obstrüksiyonu ile komplike üriner sistem infeksiyonu bulunan 30 hastada denendi. Hastalann tamamına operasyondan bir gün önce 2 gr sulbaktamla kombine 2 gr sefoperazon total günlük doz olarak başandı. Tedaviye daha sonra beş gün süre ile aynı doz günde iki defada İV yolla verilerek devam edildi. İzole edilen bakterilerde %90 oranında eradikasyon sağlanırken önemli bir yan etkiye rastlanmadı. Sonuç olarak bakteriyolojik ve klinik veriler bu kombinasyonun üriner sistem infeksiyonlarında etkili ve güvenilir olduğunu gösterdi.
Komplike Üriner Sistem İnfeksiyonlarinin Tedavisinde Sulbaktam+Sefoperazon
Keywords: Urology; Üroloji